The addition of zinc to the ICIE16-bioactive glass composition enhances osteogenic differentiation and matrix formation of human bone marrow-derived mesenchymal stromal cells - Rehder, Felix; Arango-Ospina, Marcela; Decker, Simon; Saur, Merve; Kunisch, Elke; Moghaddam-Alvandi, Arash; Renkawitz, Tobias; Boccaccini, Aldo R.; Westhauser, Fabian (Biomimetics, 2024)
An ICIE16-bioactive glass (BG) composition (in mol%: 49.5 SiO2, 6.6 Na2O, 36.3 CaO, 1.1 P2O5, and 6.6 K2O) has demonstrated excellent in vitro cytocompatibility when cultured with human bone marrow-derived mesenchymal stromal cells (BMSCs). However, its impact on the development of an osseous extracellular matrix (ECM) is limited. Since zinc (Zn) is known to enhance ECM formation and maturation, two ICIE16-BG-based Zn-supplemented BG compositions, namely 1.5 Zn-BG and 3Zn-BG (in mol%: 49.5 SiO2, 6.6 Na2O, 34.8/33.3 CaO, 1.1 P2O5, 6.6 K2O, and 1.5/3.0 ZnO) were developed, and their influence on BMSC viability, osteogenic differentiation, and ECM formation was assessed. Compared to ICIE16-BG, the Zn-doped BGs showed improved cytocompatibility and significantly enhanced osteogenic differentiation. The expression level of the osteopontin gene was significantly higher in the presence of Zn-doped BGs. A larger increase in collagen production was observed when the BMSCs were exposed to the Zn-doped BGs compared to that of the ICIE16-BG. The calcification of the ECM was increased by all the BG compositions; however, calcification was significantly enhanced by the Zn-doped BGs in the early stages of cultivation. Zn constitutes an attractive addition to ICIE16-BG, since it improves its ability to build and calcify an ECM. Future studies should assess whether these positive properties remain in an in vivo environment.
Gesehen am 29.08.2024